Optimizing the safety and efficacy of the awake venovenous extracorporeal membrane oxygenation in patients with COVID-19-related ARDS - Sklienka, Peter; Burša, Filip; Frelich, Michal; Máca, Jan; Vodička, Vojtech; Straková, Hana; Bílená, Markéta; Romanová, Tereza; Tomášková, Hana (Therapeutic advances in respiratory disease, 2024)
BACKGROUND: Maintaining the patient awake and not intubated during the venovenous extracorporeal membrane oxygenation (VV ECMO) reduces the risk of ventilation-induced lung injury in patients with ARDS. Currently, there is a lack of data on outcomes and complications associated with the awake ECMO approach. OBJECTIVES: To evaluate outcomes and the occurrence of complications of awake ECMO approach guided by local safety protocol comprising ultrasound-guided cannulation, argatroban-based anticoagulation, respiratory support, and routine sedation targeted to reduce respiratory effort and keeping nurse-to-patient ratio of 1:1. DESIGN: A single-center retrospective case series analysis. METHODS: Consecutive patients with COVID-19-related acute respiratory distress syndrome (ARDS) (CARDS) treated by full awake VV ECMO approach from April 2019 to December 2023 were eligible. RESULTS: Our center treated 10 patients (mean age 54.7 ± 11.6 years) with CARDS with an awake ECMO approach. The reasons for awake ECMO included the presence of barotrauma in six patients, a team consensus to prefer awake ECMO instead of mechanical ventilation in three patients, and the patient's refusal to be intubated in one case. Before ECMO, patients were severely hypoxemic, with a mean value of Horowitz index of 48.9 ± 9.1 mmHg and a mean respiratory rate of 28.8 ± 7.3 breaths per minute on high-flow nasal cannula or noninvasive ventilation support. The mean duration of awake VV ECMO was 558.0 ± 173.6 h. Seven patients (70%) were successfully disconnected from ECMO and fully recovered. Intubation from respiratory causes was needed in three patients (30%), all of whom died eventually. In total, three episodes of delirium, two episodes of significant bleeding, one pneumothorax requiring chest tube insertion, and one oxygenator acute exchange occurred throughout the 5580 h of awake ECMO. No complications related to cannula displacement or malposition occurred. CONCLUSION: The awake ECMO strategy guided by safety protocol appears to be a safe approach in conscious, severely hypoxemic, non-intubated patients with COVID-19-related ARDS.
Keywords: intervenční ultrasonografie; Humans; lidé středního věku; mimotělní membránová oxygenace; syndrom dechové tísně; kyseliny pipekolové; Female; Aged; dospělí; sulfonamidy; bdění; výsledek terapie; senioři; lidé; Respiratory Distress Syndrome; Extracorporeal Membrane Oxygenation; Ultrasonography, Interventional; Arginine; Adult; COVID-19; ženské pohlaví; Pipecolic Acids; Male; Middle Aged; Retrospective Studies; Wakefulness; Treatment Outcome; arginin; retrospektivní studie; mužské pohlaví; antikoagulancia; Anticoagulants; Sulfonamides